Efektivitas Pelatihan Visual Imagery Dan Spasial Konkret Terhadap Kemampuan Penalaran Spasial - Genta Rizki Alfaridzi; Vigie Priantika Putra Hutama (Jurnal Kajian Ilmiah, 2026)
Addressing the limitations of prior research, which has predominantly focused on the assessment of spatial ability without systematically evaluating intervention effectiveness, particularly the integration of visual imagery and concrete spatial manipulation, this study employs a post-test-only between-subjects experimental design involving 60 undergraduate students (aged 19–26), who were assigned to four groups: visual imagery, concrete spatial (non-imagery), a combination of both, and a control group. Spatial ability was assessed using Subtests 7 (Figurenauswahl) and 8 (Würfelaufgaben) of the Intelligence Structure Test (IST). Data were analyzed using the Kruskal–Wallis test, followed by Dunn’s post hoc comparisons with Holm correction. The results indicate that all intervention groups significantly outperformed the control group (p < .001), underscoring the plasticity of spatial ability in response to structured training. However, no significant differences were observed among the experimental groups on Subtest 7 (p > .05), suggesting comparable effectiveness across training modalities in two-dimensional spatial processing. In contrast, Subtest 8 revealed a significant difference between the concrete spatial group and the combined training group (p = .038), indicating the advantage of an integrative approach for tasks involving more complex three-dimensional mental rotation. Gender did not emerge as a significant moderating factor. These findings highlight the task-specific nature of spatial training effectiveness and offer practical implications for the development of cognitive interventions and visual-spatial learning strategies, particularly within non-STEM domains.